ANALISIS STRATEGI AGRIBISNIS KOMODITAS GURAMI (Osphronemus gouramy) DI KABUPATEN KEDIRI - Dona Wahyuning Laily; Raden Ahmad Djazuli; Ida Syamsu Roidah (Universitas Muhammadiyah Gresik, 2023)
This research aims to determine the performance, alternatives, and strategic priorities that can be implemented. The research was conducted in Tunglur Village, Badas District, Kediri Regency. The data analysis methods used are the IFE matrix, EFE matrix, SWOT matrix, and QSP matrix. The research results show that (1) the main driver for the development of the Gurami fishing industry in Kediri Regency is focused on expansion. Meanwhile, the most basic weakness is limited capital. The main opportunity is that many parties support the development of gourami fish commodities, while the biggest threat is the increase in prices of production factors. (2) Eight alternative strategies are proposed, namely two S-O strategies, two W-O strategies, two S-T strategies, and two W-T strategies. 3) The final strategic priority is to maintain the market and further strengthen relationships with stakeholders to invest in developing the gourami fish industry.